Efek Struktur Modal, Ukuran Peusahaan dan Struktur Kepemilikan Saham Terhadap Nilai Perusahaan - Basmar, Nur Azizah; Mispa, Sitti; Sahidah, Sahidah (Jurnal Unicorn ADPERTISI, 2025)
Company value is the result of company performance which reflects the share price which is formed by the relationship between supply and demand in the stock market. The aim of this research is to determine the influence of capital structure, company size and share ownership structure on company value. Data collection in this research uses secondary data obtained from financial reports published and published by the Indonesia Stock Exchange using Purposive Sampling Techniques. The population in this research is pharmaceutical subsector manufacturing companies registered with Buesa Efek Indonesia in 2019- 2022, namely 11 companies. The research sample used was 33 sample data. The results of this research variable data have been tested using classic assumption tests in the form of normality, multicollinearity and heteroscedasticity assumption tests. The data analysis method uses multiple linear regression techniques. The research results show that the Capital Structure variable has no effect on Company Value, Company Size has a negative and significant effect on Company Value, and Institutional Share Ownership has no effect on Company Value.